AR-Speaking Buddy: Designing Content and User Interface of An Augmented Reality (AR)-Based Application for Malaysian Children Speaking Practice - Marzita binti Hj Mansor, Suliana binti Sulaiman, Rohaizah binti Abdul Wahid, Saira Banu binti Omar Khan, Asma Hanee binti Ariffin (Tanjung Malim, 2024)
AR-Speaking Buddy: Designing Content and User Interface of An Augmented Reality (AR)-Based Application for Malaysian Children Speaking Practice by Marzita binti Hj Mansor, Suliana binti Sulaiman, Rohaizah binti Abdul Wahid, Saira Banu binti Omar Khan, Asma Hanee binti Ariffin